Early neurological deterioration after thrombolysis: Clinical and imaging predictors. Issue 7 (October 2016) - Simonsen, Claus Z; Schmitz, Marie L; Madsen, Mette H; Mikkelsen, Irene K; Chandra, Ronil V; Leslie-Mazwi, Thabele; Andersen, Grethe
Background: National Institutes of Health Stroke Scale is the most common scale used in stroke patients. An increase of four points or more within 24 h signifies early neurological deterioration. We aimed to establish how often early neurological deterioration occurs in a cohort selected by magnetic resonance imaging and which factors predicted early neurological deterioration. Methods: In this single-center study, we collected epidemiological, imaging and outcome data on 569 consecutive patients undergoing reperfusion therapy after magnetic resonance imaging selection. Results: Of these, 33 (5.8%) experienced early neurological deterioration. Seven were due to a symptomatic intracerebral hemorrhage, 23 were caused by extension of ischemia on follow-up imaging and three were due to progression on the basis of small vessel disease. Early neurological deterioration was predicted by a larger perfusion lesion, higher blood glucose and presence of large vessel disease. Penumbra occurred in 34% of patients but only 9% of patients with penumbra experienced early neurological deterioration, thus eroding the value of penumbra as an imaging marker. Early neurological deterioration was a poor prognostic sign. Odds ratio for disability or death was 14.9 (95% confidence interval: 6.5–34.0). Conclusion: Early neurological deterioration is rare. It originates mainly from ischemic infarct growth rather than from hemorrhage. Concern should be highest in patients with elevated blood glucose, larger perfusion lesions and large vessel disease. Prior aspirin use increases risk of symptomatic intracerebral hemorrhage.